Peran Foodvloger Sebagai Preferensi Konsumtif Generasi Z Di Kota Pekanbaru - Rafli Nanda Utama; Teguh Widodo (Jurnal Ilmiah Wahana Pendidikan, 2026)
he current development of information and communication technology, particularly social media, has changed people's consumption patterns, especially among Generation Z. Food vloggers as digital influencers play a significant role in shaping consumer preferences through engaging and informative content. This study aims to analyze the role of food vloggers in shaping Generation Z's consumer preferences in Pekanbaru City, Riau, and to identify factors that make this generation easily influenced. Using a descriptive qualitative approach, data were collected through in-depth interviews, observations, and documentation from key informants and key informants who are active Generation Z on social media. The results show that food vloggers act as agents of socialization, symbol shapers, and creators of hyperreality, which encourages Generation Z to follow culinary trends as part of a modern lifestyle. The main influencing factors are symbolic consumption, such as food as a marker of social status and an effort to establish self-identity, as well as hyperreality that creates a pseudo-reality through evocative visuals and narratives. Analysis using Jean Baudrillard's hyperreality theory and George Herbert Mead's symbolic interactionism reveals how digital content shapes impulsive and excessive consumption patterns. This study recommends that Generation Z be more selective in absorbing information, while food vloggers need to maintain the honesty of their content to prevent the negative impacts of consumerism.